Persepsi Masyarakat terhadap Agroekowisata Untuk Pelestarian Fungsi Waduk Jaro - Murjani Murjani; Athaillah Mursyid; Asmuri Achmad; Chatimatun Nisa (Rawa Sains: Jurnal Sains STIPER Amuntai, 2016)
In order that Waduk Jaro remain stable, but economically produce, including through tourism approach agroecototurism. Cultivation are including the vast landscape of green as the most attractive mountains, and waterfalls spewing water and the most attractive. This research is kind or survey research using multistage sampling, where is society of sub district Jaro, district Tabalong, South Borneo Province selected with purposive sampling, from nine vilage chossing three village with reservoir location on three village (Nalui, Jaro and Garagata) taking sample at those three village using simple random sampling, where is respondence who will be chosen is head of family and visitor or tourist taking with accidental sampling, that is technique taking sample accidentally with interviewing visitor or tourist who come to location Waduk Jaro. The result shows that the perception of society which living around Waduk Jaro shows 93,6% respondence says agree that Waduk Jaro becoming tourist destination, 4,3% disagreed and 11,1%claimed not to know and 1,0% did not comment. From 94 respondence who interview, 89,4% says agree if forms of tourism which developing is agroecotourism, 5,3% says do not agree, 2% says do not know and 3,2% do not comment. Respondence from visitor or tourist society who visiting to Waduk Jaro, 98,3% agree becoming object tourism and 1,7% do not agree. And than 95,0% agree about forms of tourism which developing is agroecotourism, 3,3% did not agree and 1,7% not comment